Innovative Use of Wood Ash for Fluoride Removal from Water: Comprehensive Experiments and Mechanism Insight - Lee, Jae In; Kang, Jin Kyu; Jeong, Sanghyun; Lee, Chang Gu; Choi, Joon Weon; Park, Seong Jik (Applied Sciences (Switzerland), 2025)
This study investigates the potential of wood ash (WA), a by-product of wood-based energy production, as an eco-friendly alternative for removing fluoride from water. Kinetic analysis revealed that WA enables rapid fluoride removal, reaching equilibrium within 1 h (112.09 ± 3.9 mg/g). Equilibrium analysis demonstrated that WA exhibits a Langmuir maximum capacity of 157.34 mg/g, indicating a high adsorption capacity that ranks within the top 10% of reported adsorbents (34th out of 328). According to thermodynamic analysis, the adsorption process appears to be both endothermic and spontaneous at elevated temperatures. pH dependence studies showed that while the fluoride adsorption capacity of WA peaked under acidic conditions, it remained relatively stable (116.01 ± 0.8 mg/g) over a wide range of pH levels (5 to 11). An optimal dosage of 6.67 g/L achieved a greater than 98% fluoride removal rate. Coexisting anions affected the fluoride adsorption capacity of WA, with the order of influence being PO43− > CO32− >> SO42− > NO3− ≈ Cl−. Mechanistic analyses confirmed the surface precipitation of CaF2 as the primary mechanism responsible for fluoride removal. With a Ca content of over 66 wt.%, WA facilitates enhanced fluoride removal. Overall, this study highlights the efficacy of WA as a sustainable adsorbent for the removal of fluoride from water, contributing to the valorization of WA in wastewater treatment applications.
Keywords: Adsorption capacities; Eco-friendly; Energy by-products; Energy productions; Fluoride; Fluoride adsorptions; Fluoride removal; Green adsorbent; Kinetic analysis; Wood ash; energy byproducts; fluoride; fluorite; green adsorbent; wood ash